Effects of 17ß-Estradiol and Endocrine Disruptor Methoxychlor in Spermatogonial Stem Cells: a Protective Effect of Regucalcin? - Feijó, Mariana Pombal (2017)
Endocrine disrupting chemicals (EDCs) are a set of compounds, either natural or produced by man, that interfere with the endocrine function by altering hormone metabolism, synthesis, and mechanism of action. In the last years, estrogens have emerged as important regulators of germ cell fate, although, the beneficial or detrimental effects of these hormones in spermatogenesis remains controversial, which raised the concern about the EDCs with estrogenic behavior. Methoxychlor (MXC) is an insecticide extensively used in the agricultural sector, which displays endocrine disrupting activity by mimicking estrogens actions (xenoestrogenic). Although it has been proved that MXC can affect the male reproductive function, little is known regarding the impact of this EDC in the spermatogonial stem cell (SSCs) population. SSCs are the adult stem cell population in the testis, having self-renewal capability and high differentiation rates, and its biological activity is the foundation of spermatogenesis. Therefore, any threat disturbing SSCs population can have a detrimental impact on the spermatogenic output and male fertility. Regucalcin (RGN) is a calcium (Ca2+)-binding protein that has been associated with the control of cell proliferation, oxidative stress, apoptosis, and metabolism. Furthermore, the protective role of RGN for the germ cell population upon exposure to damaging factors, such as oxidative stress, apoptosis inducers, freezing, and radiation has been suggested. So, it is highly likely to hypothesize that RGN may have a similar behavior against EDCs actions in SSCs. In the present dissertation, the impact of 17?-estradiol (E2) and MXC on SSCs glycolytic metabolism and survival/apoptosis and the influence of RGN in attenuating their effects were evaluated. For this purpose, a rat spermatogonial stem cell line (GC-6spg) transfected to overexpress RGN (GC6-spg/RGN) was cultured. After confirming RGN overexpression by means of Western blot analysis and immunofluorescence, GC6-spg/RGN cells and mock-transfectants (GC-6spg/Mock) were exposed either to 100 nM of E2 or 25 µM of MXC for 48 hours. Glucose consumption and lactate production, as well as, the expression and activity of glycolytic metabolism and apoptosis regulators were evaluated by spectrophotometric assays and Western blot analysis. The results obtained showed an increased glycolytic activity in GC-6spg cells overexpressing RGN (GC-6spg/RGN) compared to the mock-transfectants, regardless of E2 or MXC treatments, as indicated be the augmented glucose consumption and lactate production. E2 treatment did not affect the glycolytic metabolism of GC-6spg cells, though, in the case of MXC exposure, an enhanced glycolytic metabolism was shown. Nevertheless, RGN overexpression diminished the effect of MXC. Concerning apoptosis, it was found that GC-6spg/RGN cells displayed diminished apoptosis compared with mock-transfectants, namely, by the observed diminution of Bax (proapoptotic)/Bcl-2 (antiapoptotic) protein ratio, p53 expression and caspase-3 activity. E2 also seems to decrease the apoptotic rate of GC-6spg cells whereas upon MXC treatment apoptosis was increased. Interestingly, overall, RGN overexpression tended to counteract E2 and MXC effects over apoptosis. The present study is the first evidence that SSCs metabolism and apoptosis can be modulated by hormonal factors, namely E2 and the EDC with xenoestrogenic properties, MXC. Indeed, MXC was shown to greatly change the apoptotic status and metabolism of GC-6spg cells, with E2-treatment displaying mild effects. Furthermore, RGN was identified as a possible protective mechanism against the damaging effects of MXC in GC-6spg cells. Although preliminary, the obtained findings also highlight for the impact that MXC exposure might have disrupting the SSCs population and compromising male fertility.